2019
DOI: 10.1016/j.arrct.2019.100019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Mass Index on Functional Outcome of Patients With Knee Replacement

Abstract: Objective To investigate the effects of body mass index (BMI) on the rehabilitation process in patients with a recent knee replacement. Design This retrospective cohort study included all patients admitted to a rehabilitation hospital, with a recent diagnosis of knee replacement and available hospital admission data including height and weight, between 2014 and 2017. Setting Rehabilitation hospital. Participants St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…One additional article was identified from citation search and 210 full‐text articles were assessed for eligibility. Finally, 91 studies were included, with 22 prospective, 4,7,8,16,22–39 54 retrospective, 6,9–12,14,15,17,40–85 and 15 case‐controlled studies 5,13,18,19,86–96 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One additional article was identified from citation search and 210 full‐text articles were assessed for eligibility. Finally, 91 studies were included, with 22 prospective, 4,7,8,16,22–39 54 retrospective, 6,9–12,14,15,17,40–85 and 15 case‐controlled studies 5,13,18,19,86–96 …”
Section: Resultsmentioning
confidence: 99%
“…There was 68.8% ( n = 239 897 of 348 585) females in the obese group and 62.9% ( n = 522 543 of 830 959) females in the non‐obese group. Fifty‐eight studies reported mean age at index TKA for both groups, ranging from 59.6 66 to 71.5 years 11 in the obese group, and from 58.0 93 to 74.6 years 44 in the non‐obese group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Several additional studies, however, have shown that regardless of BMI category, individuals had similar or equivocal outcomes following TKA. [28][29][30] Furthermore, it is still unknown if BMI affects early phase mobility outcomes and functions during post-TKA rehabilitation. As a result, the current study investigated the effect of BMI on early phase mobility and functional outcome during post-TKA rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…because of such reasons surgery is postponed till the weight reduction is achieved. The guidelines of American academy of orthopaedic surgeons and United Kingdom National Health Service suggest caution and rejection of surgery should be based on BMI (Burke et al, 2019b).…”
Section: Fim Scoresmentioning
confidence: 99%